Mudanças relacionadas à idade dos neurônios mioentéricos miosina V, CGRP e VIP imunoreativos do íleo de ratos suplementados com ácido ascórbico - Veit, Ana Paula Tonon (2010)
The Enteric Nervous System is composed by a variety of neurons organized in two ganglionated main plexus, myenteric and submucous, responsible for the control of several gastrointestinal functions: motility, secretion, blood flow, mucosal growth and aspects of the local immune system. Aging is a complex process influenced by genetic structure of the individual, lifestyle and environment. It results from damage to molecules, cells and tissues which gradually lost their ability to adapt or repair damage. Several gastrointestinal diseases are associated to the aging, resulting in impaired function of the mucosa and/or motility of the gastrointestinal tract, which depending on the affected area, can lead to disorders such as dysphagia, gastroesophageal reflux disorders, difficulty in relaxation of gastric fundus during the food intake, atrophic gastritis, delaying the digestive period, intestinal diverticula, diarrhea and fecal incontinence. The objective of this study was to investigate the effect of ascorbic acid supplementation on general myenteric neurons population (myosin-V immunoreactive) and sub-populations of inhibitory neurons (Calcitonin Gene Related Peptide-CGRP and vasoactive intestinal peptide VIP-immunoreactive) in rats aging process. Eighty-five male rats 90 days-old were divided in two groups: rats with 90 days-old (E90), control rats with 345 days-old (E345), control rats with 428 days-old (E428), rats treated with ascorbic acid of 90° to 345° day-old (EA345) and rats treated with ascorbic acid of 90° to 428° day-old (EA428). Treatment with ascorbic acid was conducted for 255 days (group EA345) and 338 days (group EA428), water being added daily to the animals (1g / L) on an ad libitum. After this period, the ileums of the animals were subjected to immunohistochemistry techniques (myosin-V and nNOS). The images were captured in a 20X objective. For the analysis of varicosities of neurons that express CGRP and to the VIP area was measured (μm2) 400 varicosities in each animal (2400/grupo). Ten images of myosin neurons were quantified per animal. The morphometry was performed by measuring the cell bodies of neurons (500/grupo). Aging promoted a reduction the numbers of neurons immunoreactive myosin V and changed the size of the varicosities of VIP-IR neurons and CGRP-IR. Supplementation with ascorbic acid had a neurotrophic effect on all neurons studied, suggesting a neuroprotective role.